2018
DOI: 10.1016/j.neuropharm.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate causes persistent deficits in memory and executive function in a juvenile animal model

Abstract: Methotrexate is a dihydrofolate reductase inhibitor widely employed in curative treatment for children with acute lymphoblastic leukemia (ALL). However, methotrexate administration is also associated with persistent cognitive deficits among long-term childhood cancer survivors. Animal models of methotrexate-induced cognitive deficits have primarily utilized adult animals. The purpose of present study is to investigate the neurotoxicity of methotrexate in juvenile rats and its relevant mechanisms. The doses and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 43 publications
4
16
0
Order By: Relevance
“…In the present study, the authors examined the histological changes in the cerebral cortex after administration of MTX and the improvement effect of wheat germ oil on these variations. The intraperitoneal administration of MTX induced the degeneration of most of granular and pyramidal neurons and the neuroglia, this result is consistent with 57,58 who reported that methotrexate suppresses the neurogenesis and induces microglial inflammation. Sieklucka et al studied the damage of white matter in the brain of albino swiss mice after a single intraperitoneal injection of MTX 59 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, the authors examined the histological changes in the cerebral cortex after administration of MTX and the improvement effect of wheat germ oil on these variations. The intraperitoneal administration of MTX induced the degeneration of most of granular and pyramidal neurons and the neuroglia, this result is consistent with 57,58 who reported that methotrexate suppresses the neurogenesis and induces microglial inflammation. Sieklucka et al studied the damage of white matter in the brain of albino swiss mice after a single intraperitoneal injection of MTX 59 .…”
Section: Discussionsupporting
confidence: 89%
“…This result was also observed in previous literature which declared that (ROS) generation altered neurotransmission 68 and/or induced structural brain alterations 13 while also causing mitochondrial damage which in turn causes rapid degeneration of the cells 69 and plays an important role in pathogenesis of neurodegenerative disorders, cancer and aging [21][22][23] . In addition, 57 revealed that methotrexate induced changes in neuroinflammatory markers and cellular proliferation, along with structural changes in the corpus callosum in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…A better statistically significant result with MTX versus placebo was also found in the trial [ 86 ]. Microglial activation and corpus callosum were detected in a juvenile rodent model study and it also showed cognitive decline after 1 week and 8 weeks of methotrexate 0.5 mg/kg injection [ 87 ]. An improvement in HAQ-DI (mean 1.46 from baseline 1.63; p = 0.001) in 3 months is seen in RA patients treated with leflunomide [ 88 ].…”
Section: Mechanisms Of Depression In Ra: Effects Of Inflammatory Cytomentioning
confidence: 99%
“…Besides, methotrexate increases renal folate excretion and inhibits folate uptake into the CSF [27]. The acute rise in CSF Tau after intrathecal methotrexate could be attributed to reduced CSF folate levels during the induction phase [17,18,25,[27][28][29][30]. Despite continued intrathecal and intravenous methotrexate, CSF Tau significantly declined after systemic folinic acid supplementation, which suggests that the supplementation indeed attenuates the toxicity of the anti-folate regimen.…”
Section: Discussionmentioning
confidence: 99%